Assessing the growth of preterm infants using detailed anthropometry. (9th April 2017) - Ashton, James J.; Johnson, Mark J.; Pond, Jenny; Crowley, Philippa; Dimitrov, Borislav D.; Pearson, Freya; Beattie, R. Mark
Abstract: Aim: Preterm infants display altered body composition compared to term infants, and weight gain is a crude indicator body composition. Childhood mid‐upper arm circumference (MUAC) is a measure of nutritional status. This study investigates MUAC and mid‐thigh circumference (MTC) to monitor growth in preterm infants. Methods: Preterm infants (<30‐week gestation) were recruited. MUAC, MTC, weight, length and head circumference (HC) were measured at recruitment and weekly intervals until discharge. Descriptive, correlation and regression analyses were used. Results: Ninety‐three infants were recruited. Median measurement duration was eight weeks (1–19). Median gestational age was 27 weeks (23–29). Analysis by curve estimation displayed a mean increase of 2.58 mm/week (left MUAC) (p ≤ 0.0001), 2.56 mm/week (right MUAC) (p ≤ 0.0001), 4.16 mm/week (left MTC) (p ≤ 0.0001), 4.20 mm/week (right MTC) (p ≤ 0.0001). Coefficients of determination (R 2 ) were calculated using a growth regression model for MUAC and MTC (0.866–0.917); measures were comparable to growth modelling of weight (0.913), length (0.945) and HC (0.928). High concordance between left and right MUAC and MTC generated a Pearson's correlation coefficient of 0.999 (MUAC) (p ≤ 0.001) and 0.994 (MTC) (p ≤ 0.001). Conclusion: Data demonstrate the potential utility of MUAC and MTC as additional measures of growth in preterm infants that are reproducible over time. There is potential to gain insights to improve lean‐mass accretion in preterm infants.